Pulsos de inundação controlam a variabilidade e persistência da comunidade de Ostracoda (Crustacea)? Estudo de longa duração em um ambiente lêntico de planície tropical. - Conceição, Eliezer de Oliveira da (2017)
Large rivers in tropical regions have strong variation of abiotic factors due to occurrence of flood pulses. Dams and natural events control the intensity and duration of these pulses. The hypothesis tested was that the Ostracoda community is persistent at regular pulses and more variable at extreme flood. Thus, the ostracods were monitored in a lentic environment of the upper Paraná River floodplain during 83 months (seven hydrologic cycles). The alteration of the water level directly influenced the abiotic variables, and these were correlated with the composition and abundance of ostracods (PCoA). The variability of the species composition was observed among several hydrological cycles, and only the extreme flood distinguished from its previous cycle. The absence of significant differences in community variability between succeeding periods indicates its persistence to natural pulses or short durations, probably because this community has developed adaptations that minimize its effects. The long duration and oscillation of the extreme flood influenced the variation of the environmental conditions reflecting the greater variability of the composition of ostracods in this hydrological period.